Modern-day public space in the historical context of a city - new development of the Cathedral Square (Domplatz) in Hamburg = Współczesna przestrzeń publiczna w historycznym kontekście miasta - nowe zagospodarowanie Placu Katedralnego (Domplatz) w Hamburgu - Jóźwik, Renata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the history of transforming one of the oldest places in Hamburg - the Cathedral Square (Domplatz), as well as the influence of historical factors on the conception behind its development. A tumultuous history, especially the consequences of World War II, has led to the diminishment of its historical significance. The undeveloped quarter once occupied by a prehistoric settlement and St. Mary's Cathedral functioned as an urban wasteland and a parking lot for a few decades.
Keywords: współczesna przestrzeń placu; historyczna tożsamość miejsca; Hamburg; current area of square; historical identity of a location